Glucocorticoids and mineralocorticoids in hair: facilitating accurate diagnosis of adrenal-related endocrine disorders - Heyns, Bianca; Pieters, Rialet; Stander, Marietjie Aletta; Atkin, Stephen Lawrence; Swart, Amanda Cecilia (Frontiers in Endocrinology, 2024)
Glucocorticoids and androgens in the hair follicle have been of interest for many years, particularly cortisol and cortisone in retrospective studies associated with chronic stress and Cushing's syndrome. No studies have reported aldosterone or 18-hydroxycorticosterone in the adrenal mineralocorticoid panel in the hair follicle. This study aimed to identify potential biomarkers in endocrine conditions associated with steroid excess or deficiency using a novel extraction protocol in the analysis of mineralocorticoids and glucocorticoids in the hair follicle.Hair was collected from 15 healthy male and female volunteers. Segments that were cut along the length of long, medium and short hair and segments shaved on the scalp and the cheek were prepared for analysis. Hair samples were extracted using an automated accelerated solvent extraction system. Steroids were analyzed using high-throughput ultra-performance convergence chromatographytandem mass spectrometry. All mineralocorticoids and glucocorticoids were detected above the lower limit of quantification and none of the steroids differed statistically comparing male and female concentrations. Deoxycortisol, deoxycorticosterone and aldosterone were detected for the first time in males. In both genders, 18hydroxycortisosterone was detected for the first time. The median concentrations for females and males, respectively, were deoxycortisol, 14.2 and 19.